2000
DOI: 10.1002/(sici)1099-1050(200001)9:1<9::aid-hec471>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between marijuana initiation and dropping out of high school

Abstract: The prevalence of marijuana use among young people has risen rapidly in recent years, causing concern over the potential impact on academic performance of such use. While recent studies have examined the effect of alcohol use on educational attainment, they have largely ignored the potential negative effects of other substances, such as marijuana. This paper examines whether the relationship between the initiation of marijuana use and the decision to drop out of high school varies with the age of dropout or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
102
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(116 citation statements)
references
References 29 publications
8
102
0
6
Order By: Relevance
“…Under this hypothesis, individuals who begin smoking cannabis at an early age, for whatever reason, are less motivated to pursue an education (which would be consistent with our observations in Table 1, as well as those of other investigators (Bray et al, 2000;Hammer and Vaglum, 1990;Lynskey and Hall, 2000)), and would thus remain particularly disadvantaged on tests requiring verbal abilities. This prediction is consistent with our observation that early-onset users were sharply distinguishable from controls primarily on tests requiring verbal abilities, including VIQ itself, memory of word lists on the BSRT, and semantic categories on the FAS test.…”
Section: Discussionsupporting
confidence: 87%
“…Under this hypothesis, individuals who begin smoking cannabis at an early age, for whatever reason, are less motivated to pursue an education (which would be consistent with our observations in Table 1, as well as those of other investigators (Bray et al, 2000;Hammer and Vaglum, 1990;Lynskey and Hall, 2000)), and would thus remain particularly disadvantaged on tests requiring verbal abilities. This prediction is consistent with our observation that early-onset users were sharply distinguishable from controls primarily on tests requiring verbal abilities, including VIQ itself, memory of word lists on the BSRT, and semantic categories on the FAS test.…”
Section: Discussionsupporting
confidence: 87%
“…Other studies in general have not considered both cannabis and tobacco use by young people and subsequent educational outcomes in the same cohort; rather, they have reported the effects of cannabis use adjusted for tobacco use. A small number of previous studies have considered the effects of tobacco use on educational attainment, and have reported similar patterns of association to those that we observed 24, 25, 26, 27. The associations for cannabis were found to be non‐specific; due to tobacco use by age 15 showing very similar patterns of association with the same educational outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…Third, the study may actually underestimate the prevalence of cannabis use among adolescents, considering that those who have dropped out of school may have particularly high rates of frequent cannabis use. 33 Finally, although the class response rate was high (88%), the student participation rate was relatively low (59%) and may have negatively affected the external validity of the results. However, the data did not show evidence of appreciable nonresponse bias.…”
Section: Strengths and Limitationsmentioning
confidence: 99%